A PROSPECTIVE STUDY OF CONTRASTING PERFORMANCE OF MITOMYCIN-C INSTILLATION IN A SINGLE SESSION TO THAT OF SIX SESSIONS IN PATIENTS WITH LOW-RISK, NON-MUSCLE-INVASIVE BLADDER CANCER (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The effectiveness of intravesical instillation in preventing recurrence and development of non-muscle-invasive bladder cancer was demonstrated following transurethral excision of low-grade and low-stage tumors. Methods and patients: A prospective randomized controlled trial included 48 individuals with low-risk non-muscle-invasive bladder cancer. All patients were considered as long as their tumors were single papillary and 3 cm or smaller; those with muscle invasion, G3 tumors, bladder carcinoma in situ, or tumors that had been surgically removed with perforation were prohibited. After the tumor was fully removed, patients were randomly assigned to one of two groups. One group received 40 mg of mitomycin C instilled into the urinary bladder after hematuria stopped (typically within 6 hours). The other group received six sessions of mitomycin C instillation. The median follow-up for this group was 24 months. Progress, length of hospital stay, and catheterization period were among the events examined, along with recurrence-free rate, recurrence rate per year, and number of new tumors growing per year. Results: As of the 24-month follow-up, the recurrence-free rate was 93.4% in group B after six sessions of mitomycin C instillation, compared to 80.1% in group A after a single session. Group B, which received mitomycin C instillation for six sessions, had a lower recurrence rate (9.1% vs. 4.5%) and recurrence per year rate (9.85% vs. 3.3%). Group A, which had mitomycin C instillation for one session, had no such advantage. The rate of new tumors each year was marginally lower in Group B, which received six sessions of mitomycin C instillation, compared to Group A, which received one session. The advancement rate was 4.5%, and there was no statistically significant difference between the two groups. The other results were also comparable. Compared to six sessions of mitomycin C instillation, one session (Group A) was associated with a shorter hospital stay, a shorter catheterization length, a lower level of local symptoms, and a lower cost. Conclusions After surgery or within six hours of resection, a single dose of mitomycin C may be just as effective as a six-dose regimen. The six-session plan may save money by avoiding unnecessary hospitalization and catheterization. Hence, this method can be used instead of the six sessions of mytomycin C instillations or observation. Immediate mitomycin C instillation, often within 6 hours following TURBT, may restrict cell implantation as a mechanism of early recurrence, according to this study. Aim of the study: The purpose of this study is to evaluate the effects of mitomycin C given once versus six times after transurethral removal of a bladder tumor on the rates of recurrence and progression in patients with low-risk, non-muscle-invasive bladder cancer.
Keywords: Mitomycin C, bladder cancer, Transurethral resection, patients with low-risk.